Adsorptive removal of hazardous rhodamine B dye from aqueous solutions by St. John's wort (Hypericum perforatum) - Isik, Birol (SPRINGER HEIDELBERG, 2025)
In this work, it was aimed to remove the highly toxic rhodamine B (RhB) dye from wastewater by using a low-cost, renewable, sustainable, and completely natural adsorbent obtained from St. John's wort (Hypericum perforatum) (HP), which is considered an agro-waste. HP was characterized by FTIR-ATR, XRD, FESEM, and pHpzc. Adsorption experiments were conducted by optimizing pH (2-12), dose (0.01-0.30 g), time (0-120 min), and concentration (10-50 mg/L). Equilibrium data were applied to linear isotherms. The results stated that the removal process occurred in a monolayer on the homogeneous surface of HP and the q(m) value was determined as 196.08 mg/g at 298 K. Kinetic results showed that RhB adsorption on HP followed a quasi-second-order. The effect of salt concentration onto RhB adsorption on HP adsorbent and reusability studies were conducted. Thermodynamic tests showed that the process was exothermic (Delta H-A(o) = - 13.58 kJ/mol (Delta G(A)(o) = - 26.61 kJ/mol ). The results of the study indicated that HP may be a favorable adsorbent for basic dyes in wastewater.
Keywords: Adsorption; Agro-waste; St. John's wort; Rhodamine B; ADSORBENT; Energy & Fuels; Engineering